Recessionary changes at work and employee well-being: The protective roles of national and workplace institutions. (December 2019) - Ogbonnaya, Chidiebere; Gahan, Peter; Eib, Constanze
The recession following the 2008 financial crisis brought major changes to employees' experiences at work. We investigate the adverse effects of two of such changes: perceived organizational distress and job deterioration. We also examine the extent to which institutions at national level (employment protection legislation and collective bargaining coverage) and at workplace level (employment contract and union membership) may act as buffers against these effects. Using data from 21 European countries, we show that recessionary changes were associated with reduced psychological well-being and greater levels of work–nonwork interference.